Optimization of fertilizer requirement for broccoli under field condition (Bangladesh Journal of Agricultural Research, 2008)
DOI: http://dx.doi.org/10.3329/bjar.v32i3.550Bangladesh J. Agril. Res. 32(3) : 487-491, September 2007